A unique gut microbiota signature in pulmonary arterial hypertension: A pilot study. (28th February 2022) - Jose, Arun; Apewokin, Senu; Hussein, Walaa E.; Ollberding, Nicholas J.; Elwing, Jean M.; Haslam, David B.
Abstract: Pulmonary arterial hypertension (PAH) is a progressive, ultimately fatal cardiopulmonary disease associated with a number of physiologic changes, which is believed to result in imbalances in the intestinal microbiota. To date, comprehensive investigational analysis of the intestinal microbiota in human subjects is still limited. To address this, we performed a pilot study of the intestinal microbiome in 20 PAH and 20 non‐PAH healthy control subjects, recruited from a single center, with each PAH subject recruited simultaneously with a cohabitating non‐PAH control subject. Shotgun metagenomic sequencing was used to analyze the microbiome profiles. There were no differences between PAH and non‐PAH subjects across several measures of microbial abundance and diversity (Alpha Diversity, Beta Diversity, F/B ratio). The relative abundance of Lachnospiraceae bacterium GAM79 was lower in PAH stool samples as compared to non‐PAH control subject' stool. There was no strong or reproducible association between PAH disease severity and global microbial abundance, but several bacterial species (a relative abundance of Anaerostipes rhamnosivorans and a relative deficiency of Amedibacterium intestinale, Ruminococcus bicirculans, and Ruminococcus albus species were associated with disease severity (most proximal right heart catheterization hemodynamics and six‐minute walk test distance) in PAH subjects. Our results support further investigation into the presence, significance, and potential physiologic effects of a PAH‐specific intestinal microbiome.